Phytochemicals as Modulators of Paraoxonase-1 in Health and Diseases - Zahra Najafi Arab; Danial Khayatan; Seyed Mehrad Razavi; Kimia Zare; Elnaz Kheradkhah; Saeideh Momtaz; Gianna Ferretti; Tiziana Bacchetti; Thozhukat Sathyapalan; Seyed Ahmad Emami; Amir Hossein Abdolghaffari; Amirhossein Sahebkar (MDPI AG, 2022)
Chronic diseases such as cardiovascular disease (CVD), atherosclerosis, chronic liver disease, and neurodegenerative diseases are major causes of mortality. These diseases have gained much attention due to their complications, and therefore novel approaches with fewer side effects are an important research topic. Free radicals and oxidative stress are involved in the molecular mechanisms of several diseases. Antioxidants can scavenge free radicals and mitigate their adverse effects. One of the most important antioxidant enzymes are paraoxonases (PONs). These enzymes perform a wide range of physiological activities ranging from drug metabolism to detoxification of neuroleptics. Paraoxonase-1 (PON1) is produced in the liver and then transferred to the bloodstream. It has been demonstrated that PON1 could have beneficial effects in numerous diseases such as atherosclerosis, CVD, diabetes mellitus, and neurodegenerative diseases by modulating relevant signalling pathways involved in inflammation and oxidative stress. These pathways include peroxisome proliferator-activated receptor gamma (PPAR-γ) and protein kinase B/nuclear factor kappa-light-chain-enhancer of activated B cells (AKT/NF-κB)-dependent signalling pathways. Increasing PON1 could potentially have protective effects and reduce the incidence of various diseases by modulating these signalling pathways. Several studies have reported that dietary factors are able to modulate PON1 expression and activity. This review aimed at summarizing the state of the art on the effects of dietary phytochemicals on PON1 enzyme activity and the relevant signalling pathways in different diseases.